Tensions Within the Ministry of Provenance: Reflections on Co-Creating a Research Game Together With Artists. (June 2019) - Wetzel, Richard; Bachour, Khaled; Flintham, Martin
Background. Research games are challenging to design as they seek to fulfil a research agenda as well as work as a game. We have successfullycollaborated with a group of artists in a research game about people's perception of provenance called The Apocalypse of the Ministry of Provenance (MoP). The web-based game ran for 6 months with a total of 1004 players signing up over its lifetime with 490 consenting to their data being used for research purposes. While the game allowed us to answer our provenance-related research questions, in this article we look at the game design process of such a collaborative research game. Aim. Theco-creation approach created tensions that had to be carefully negotiated between everyone involved. The purpose of this article is to investigate the nature of these tensions, what has caused them, and how we managed (or failed) to mitigate them. This leads to recommendations for future researchers co-creating a research game with artists. Method. We use the form of apost-mortem reflection on the development of the game, based on our own experiences, a one-hour long interview with the two artists involved, and post-game phone interviews with players (n=8). Results. We identify the followingthree tensions that had a high impact on the overall process: 1) Translating research questions into engaging gameplay elements; 2) Creation of research-relevant content by artists; 3) Artistic vision conflicting with research agenda. We contextualize these tensions by describingsix vignettes concerning our collaborationin rich detail that highlight the salient issues of the overall process and resulting game from different perspectives. Lastly, we presentseven mitigation strategies on how to deal with the tensions or prevent them from arising. Conclusions. A collaboration with artists for the purpose of creating a research game is a rewarding but also challenging process. Overcoming the resulting tensions is possible by utilizing mitigation strategies that need to be implemented jointly between researchers and artists to guarantee the success as an engaging research game.